Tinjauan Yuridis Terhadap Peranan Kebijakan Afirmatif Menurut Undang-Undang No. 7 Tahun 2023 Tentang Pemilihan Umum Bagi Keterwakilan Perempuan di Lembaga Legislatif - Apriliani Dewi Susana (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
The representation of women in legislative bodies is a critical issue in achieving gender justice and inclusive democracy. Law No. 7 of 2023 on General Elections regulates affirmative policies to increase women’s representation through a minimum quota of 30% in the list of legislative candidates. This study aims to analyze the role of these affirmative policies from a legal perspective, focusing on the effectiveness of their implementation and the challenges faced. The research adopts a normative juridical method, utilizing a statutory approach and document analysis. The findings reveal that although the affirmative policies are clearly regulated and have significantly increased women’s representation in legislative bodies, achieving the expected 30% representation still faces various challenges, including patriarchal culture, limited political education for women, and weaknesses in monitoring and law enforcement. In conclusion, the affirmative policies in the Election Law play a significant role in promoting women’s representation in legislative bodies, but more comprehensive strategic measures are needed to ensure their effectiveness, including capacity building for women and strengthening oversight mechanisms.